105/5000 Performance of a biodigester loaded with septic sludge and guinea pig excretion for the production of biogas and biol - Quipuzco Ushñahua, Lawrence (2011)
Ecological systems known as ECOSAN allow a complete recovery of almost all nutrients and mineral nutrients in wastewater after a separately appropriate treatment from feces, urine and greywaters contributing to reuse of biol in agriculture and bioenergy through biogas. The research was conducted in the retreat house El Milagro, located at 32 ½ Km of the Lima - Huarochirí highway in the Lurín river basin. The retreat house has an ecological sanitation system built in 2007. The blackwaters (mixture of feces, urine and toilet water) come from 15 toilets with an average flow of 362.5 liters per week. The agricultural wastes were composed of cavy manure and corn plant waste. Cavy manure was collected from the cavy farm (about 200 cavies) and corn plant wastes were collected from the fields of crops. Semi-continuous load of the biodigester was done every seven days and consisted of a mixture of cavy manure and septic sludge from Imhoff tank. The volume of mixture fed to the biodigester was 400 liters per week, with the mixing ratio of 3 to 1, that is, 300 liters of septic sludge and 100 kg of cavy manure. The biodigester reduced in three logarithmic units of faecal coliforms from 3.31x104 CFU/100 ml to 6.3x104 CFU/100 ml. With respect to parasites (helminths and protozoa) was reduced from 35 Org/l to 7 Org/l in the biol, achieving an efficiency of 80%. Biol not meet the maximum allowable concentration to be used as irrigation according to the World Health Organization, which states that the liquid used as irrigation is less than 1000 CFU/100 ml faecal coliforms and less than 1 Org/l in parasites. The percentage of BOD5 and COD removal in the biodigester was 45.5% and 69% respectively. The efficiency achieved by the biodigester is typical in Chinese biodigesters (rounds), where the short run (short diameter) no occurs significant degradation.